Analisis kedisiplinan belajar peserta didik selama pandemi pada muatan pelajaran ppkn kelas V sekolah dasar - Sindhusakti Rahman Rasyid; Hasan Mahfud; Matsuri Matsuri (Jurnal Pendidikan Dasar, 2022)
This study aims to determine the student's learning discipline attitude during the pandemic on the content of the Civics Class V lesson at the Packaging 1 Sawit State Elementary School for the 2021/2022 Academic Year with the implementation of learning having been carried out in schools.This research uses qualitative research, using a case study approach or method. Sources of data in this study were students and homeroom teachers of class V SD Negeri 1 Packaging. Data collection techniques in this study used observation, questionnaires, and interviews. The data were analyzed using the Miles and Huberman data analysis model, namely data reduction, data presentation, and drawing conclusions. The results showed that the learning discipline of fifth grade elementary school students during the COVID-19 pandemic showed high category results with indicators of discipline in entering school, discipline in following lessons at school, discipline in doing assignments, discipline in studying at home, discipline in studying at home. obey school rules. The results of the study can add to the treasures and as a reference regarding the learning discipline of students during the COVID-19 pandemic.